Analisis Produksi Dan Pendapatan Usahatani Padi Sawah di Kecamatan Dampelas Kabupaten Donggala - Sofhan Sofhan; Max Nur Alam; Rosida P. Adam (Mitra Sains, 2019)
This research aims to know factor influencing production and to know the income of wet rice field farm operation in Dampelas Subdistrict Donggala Regency. The type of this research is dectriptive. Data collection has been conducted by survey and direct observation in the field. Primary data have been collected from 41 respondents out of 411 population using simple random sampling method. The results show that production factor, land area, seed quantity, Urea and Organic fertilizer quantity have a significant effect on the increase of rice production while the NPK fertilizer and labor has a non-significant effect on increasing production. Farm income analysis results showed that the average farmer’s income once the harvest is Rp. 13.534.891per 0,97 ha or Rp. 13.960.516/ha.